Assessing the Increasing Incidence of Prostate Cancer in Urban Delhi: Risk Factors, Early Detection, and Treatment Challenges - Eric Kwasi Elliason; Atul Khajuria; Stephen Monday; J. Samuel Kamanda (International Journal of Oncological Nursing and Practices, 2025)
Background: Prostate cancer has emerged as the second most prevalent cancer among men in India, with rapidly increasing incidence rates in urban areas like Delhi. This rise is attributed to urbanization, lifestyle changes (high-fat diets, tobacco use, sedentary behavior), increased life expectancy, and improved diagnostics. Despite its growing burden, low awareness, limited screening programs, and treatment barriers hinder early detection and effective management. This study examines the epidemiological trends, risk factors, and systemic challenges in prostate cancer care in Delhi to inform targeted public health interventions. Objective: To assess the increasing incidence of prostate cancer in urban Delhi by analyzing risk factors, evaluating early detection practices, and identifying treatment barriers to guide policy and interventions. Methods: A cross-sectional study was conducted with 500 prostate cancer patients (purposively sampled) and 500 age-matched controls (stratified random sampling). Data were collected via questionnaires, interviews, and medical records, and analyzed using SPSS (descriptive statistics, chi-square tests, logistic regression) and NVivo (thematic analysis). Results: (1) Risk Factors: High tobacco use (60% smokeless, 50% smoking), sedentary lifestyles (70%), and high-fat diets (50%) were prevalent among patients. (2) Awareness: Only 30% of patients and 10% of controls knew about PSA testing; symptom awareness (e.g., difficulty urinating) was higher in patients (90%) than in controls (36%). (3) Screening: Post-campaign screening participation rose from 12 to 40%, though financial constraints (50–60%) and cultural stigma (30%) persisted. (4) Treatment Challenges: Cost (50% patients, 60% controls) and limited healthcare access hindered timely care. Conclusion: The study highlights the urgent need for multifaceted interventions, targeted awareness campaigns, subsidized screening, lifestyle modifications, and stigma reduction to address the rising prostate cancer burden in Delhi. Policy efforts must prioritize equitable access to early detection and treatment to improve outcomes.
Keywords: India; Prostate cancer; Risk factors; early detection; public health interventions; screening barriers; treatment access; urban health disparities